La paradoja de la media naranja. Los desencuentros en lo cotidiano y el derecho (Tema Central) - Ávila Santamaría, Ramiro Fernando (2018)
Society demands women and men to live together. However, at the same time, society determines different roles in men and women, so different that that ideal to live together, in practice, becomes difficult. This is the half orange paradox. Multiple testimonies of men and women from an academic community demonstrate the origin and daily experience of gender roles in different spaces and moments. Law does reflects this paradox and its dualisms. We all, men and women, lose. It urges a change of assessment of the assigned roles to achieve a more egalitarian society, with more justice and solidarity.